The Effectiveness of the State Duma Women — Deputies of the VII Convocation of the Russian Federation According to the Rating “Utility Coefficient of the State Duma Deputies” in Comparison with the CIS Countries - I. A. Vetrenko (Евразийская интеграция: экономика, право, политика)
In this article, the author examines the problems of women’s participation in politics based on an analysis of the gender composition of the deputy corps of the State Duma of the VII convocation, and also compares their activity and effectiveness with male deputies on the basis of the rating “The coefficient of utility of State Duma deputies” compiled by the deputy club since 2017 d. The data of the integral rating, consisting of four indices, make it possible to identify the strengths and weaknesses of the activities of female deputies and to identify the cause-and-effect relationships of this. The article also identifies the main trends in gender policy in the countries of the Commonwealth of Independent States and compares the representation of women in government.